Jovens urbanos na periferia de Goiânia: espaços formativos e mediações escolares - DUARTE, Aldimar Jacinto (2010)
This work is linked to the line of research entitled "State, Politics and History of Education" Program of the Graduate School of Education, Federal University of Goiás. Seeks to understand the relationship that two groups of young people belonging to lower classes, inhabitantes in the suburbs, located in Goiânia, with the city and the scholl. Part of de notion of Henri Lefebvre, Pierre Bourdieu, Marc Augé and Robert Caltel that the modern city determines how the agents live their daily lives, while establishing new ways of coping with reality.The qualitative research made use of documents relating to the true population of Goiânia, the inclusion / exclusion in Goiania, the scenario of school education in Brazil, the application of questionnaires to teachers and young people, to interviews with two groups of yong, one composed of students of adult education, and anodher by members of a group of breakdance. Final considerations show that poor young people, in their desire to move and try new experiences in urban spaces are constituted as the main victims of urban and industrial model of modernity, which leads to their discrimination and socio-spatial segregation. Demonstrate that the school institution, from the perspective of young people, has not provided a body of knowledge that would provide these officials with the inclusion in the dispute purposeful social construction of rights to live in dignity the city and the neighborhood in which they reside.